Economic burden and cost-effectiveness of moderate to severe psoriasis treatment in Asian region: a systematic review / Nurul Fatiha Risma Rismayuddin, Nor Azmaniza Azizam and Aniza Ismail - Rismayuddin, Nurul Fatiha Risma; Azizam, Nor Azmaniza; Ismail, Aniza (Universiti Teknologi MARA, 2021)
Psoriasis poses a significant economic burden. A systematic review of psoriasis treatments cost and effectiveness has been performed extensively in the United States (US) and Europe, but such review is limited in Asia. This review aims to analyze all previous literature on the cost and effectiveness of systemic and biological treatment for moderate to severe psoriasis. Cost of illness and cost-effectiveness studies that examined the economic burden, cost, and effectiveness of psoriasis treatments (systemic and biological) in Asian region from 2010 to 2020 were published in English language. All costs were converted into 2020 US Dollar. All COIs included found that direct medical costs were greater than indirect costs. Adalimumab, ustekinumab, risankizumab, secukinumab 150 mg were cost-effective treatments and of the lowest cost per PASI-75/PASI1 and/or QALY. When comparing the different treatments, topical and systemic psoriasis treatments were observed to be the most cost-effective compared with other modalities. Given the tremendous economic effects of psoriasis on patients and hospitals, economic analysis, clinicians, and policymakers should consider cost and effectiveness evidence, as this systematic literature review was conducted to analyze previous documentation regarding the cost and effectiveness of systemics and biologics in Asian countries.